Screening of Klebsiella pneumoniae Isolates for Carbapenemase and Hypervirulence-Associated Genes by Combining the Eazyplex® Superbug CRE and hvKp Assays - Jürgen Rödel; Yvonne Pfeifer; Martin A. Fischer; Birgit Edel; Sylvia Stoll; Wolfgang Pfister; Bettina Löffler (MDPI AG, 2023)
The acquisition of hypervirulence-associated genes by carbapenemase-producing Klebsiella pneumoniae is being increasingly observed, and easy-to-use diagnostic tests are needed for the surveillance of the hypervirulent K. pneumoniae (hvKp). In this pilot study, 87 K. pneumoniae isolates from invasive infections collected in 2022 and 2023 were analysed using the LAMP-based eazyplex® Superbug CRE and hvKp assays for the simultaneous identification of carbapenemases and virulence genes (rmpA/A2, iuC, iroC, ybt, clb). Nine isolates showed a Kleborate virulence score of 4 or 5 (10.3%). The time for the results of the eazyplex® assays ranged from 6.5 to 13 min, and the total turnaround time, including sample preparation, was less than 30 min. Five isolates, three of which produced New Delhi metallo-beta lactamase (NDM), were subjected to whole-genome sequencing (WGS) analysis for further characterisation. The eazyplex® test results for beta-lactamase and virulence genes were confirmed. The eazyplex® hvKp, currently only available as a Research Use Only assay, may be a useful tool for the rapid identification of hvKp without significant additional workload when combined with the eazyplex® Superbug CRE assay for the detection of carbapenemases.